2014
DOI: 10.1002/wene.113
|View full text |Cite
|
Sign up to set email alerts
|

A review of PEM fuel cell durability: materials degradation, local heterogeneities of aging and possible mitigation strategies

Abstract: Through a tight collaboration between chemical engineers, polymer scientists, and electrochemists, we address the degradation mechanisms of membrane electrode assemblies (MEAs) during proton exchange membrane fuel cell (PEMFC) operation in real life (industrial stacks). A special attention is paid to the heterogeneous nature of the aging and performances degradation in view of the hardware geometry of the stack and MEA. Macroscopically, the MEA is not fuelled evenly by the bipolar plates and severe degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
219
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(238 citation statements)
references
References 95 publications
(265 reference statements)
5
219
0
1
Order By: Relevance
“…The initiation and leak growth periods of the tests with PITM resemble those of the constant RH tests, despite being exposed to baseline AMDT conditions, including RH cycling. The longer leak growth times at constant RH and with PITM confirm that MEAs are able to operate for a relatively long time despite the presence of small leaks, when the conditions are favorable; 59 i.e., low mechanical stress in the case of constant RH and low chemical stress in the case of PITM.…”
Section: Resultsmentioning
confidence: 61%
“…The initiation and leak growth periods of the tests with PITM resemble those of the constant RH tests, despite being exposed to baseline AMDT conditions, including RH cycling. The longer leak growth times at constant RH and with PITM confirm that MEAs are able to operate for a relatively long time despite the presence of small leaks, when the conditions are favorable; 59 i.e., low mechanical stress in the case of constant RH and low chemical stress in the case of PITM.…”
Section: Resultsmentioning
confidence: 61%
“…Firstly, PEMFC materials [3][4][5] and systems 6,7 are not sufficiently durable in operation. Secondly, their catalysts are based on expensive and rare elements (generally platinum or platinum-alloys).…”
mentioning
confidence: 99%
“…Liang et al [229] found water electrolysis would take place while cell reversal results in significant performance degradation. Meanwhile, the load variation process of PEMFCs is a very complex phenomenon, which is affected by many parameters, such as reactant stoichiometric ratio [216,230], reactant flow rate [231], loading range [220], loading speed [220], anode and cathode humidity [230][231][232], anode and cathode pressure [230] and proper reactant supply system [233].…”
Section: Load Variation Processesmentioning
confidence: 99%